Relevansi Remisi Literasi Brasil untuk Pembaruan Hukum Pemasyarakatan di Indonesia - Icca Cahya Anggraeni; Emmilia Rusdiana (Faculty of Law, University of Mataram, 2026)
The paradigm shift in remission from a behavior-based to a risk-based in Law Number 22 of 2022 on Corrections with regard to conditional sentences has not been followed by its implementing regulations. Although literacy activities have been recognized in the prisoners’ development assessment system as part of intellectual development, their contribution to remission is indirect. Furthermore, the requirement to reduce the risk level cannot be implemented because it is not yet connected to the remission mechanism. This condition reflects the failure of Government Regulation Number 99 of 2012 to operationalize the new paradigm established by the law. Brazil, through CNJ Resolution Number 391 of 2021, has established literacy as the basis for granting remissions, accompanied by clear procedures. This study addresses two questions: whether the Brazilian literacy-based remission model is legally relevant as a reference for the Indonesian Correctional system, which does not yet recognize literacy as a direct basis for granting remissions, and whether the inconsistency between GR 99 of 2012 and Law 22 of 2022 creates a normative obligation for the state to revise it. This study uses normative legal research methods through a statutory approach, a conceptual approach, and a comparison with the functional model and the concept of legal transplantation to assess the feasibility of adapting the Brazilian model. The results show that the Brazilian model is relevant in three aspects: conceptual, procedural, and verification, with a note that it rejects the ideology of ressocialização. The inconsistency between GR 99 of 2012 and Law 22 of 2022 results in legal dysfunction, so the state is obliged to revise GR 99 of 2012.